A method for validating a non-hazardous canine training aid - Simon, Alison G.; Lazarowski, Lucia; Krichbaum, Sarah; Singletary, Melissa; Angle, Craig; Waggoner, Paul; Van Arsdale, Kelly; Barrow, Jason (Frontiers in Analytical Science, 2023)
Detection dogs are trained to locate a variety of substances to provide security and protection for the public and the environment, but access to substances for training is often limited. Various training aids have been created to deliver target odors as safer or more accessible alternatives to using the actual substance material, many of which are commercially available. However, the methods used to create and validate the effectiveness of these training aids are rarely reported or available to consumers, leading to uncertainty regarding their use. There has been a recent drive in the detection canine community to create standards by which to measure the manufacture and utility of canine training aids, but little progress has been made in determining how a reliable canine training aid should be developed and which analytical measurements should be utilized. While the interest in and need for an independently evaluated training aid is clear, developers typically do not release the necessary information, whether for proprietary or other reasons. Transparent analysis and procedures would allow for direct examination of training aids using objective measures, which in turn would allow canine teams to select the best tool to achieve their mission. To this end, the current manuscript provides a stepwise method for the development and validation of a novel canine training aid, using triacetone triperoxide (TATP) as an example target. This method can be applied to the creation of training aids of many different target odors, such as explosives, narcotics, chemical warfare agents, or biological diseases and viruses.